RETRACTED : SOCIAL NETWORK ANALYSIS TOWARD TWITTER'S USERS AGAINST HOAX IN INDONESIA WITH SINGLE CLUSTER MULTI-NODE METHOD USING APACHE HADOOP HORTONWORKSTM DISTRIBUTION - Karimi, Husain Faiz; Arini, Arini; Masruroh, Siti Ummi (LPPM of STIMIK ESQ, 2018)
This article has been retracted at the request of the Editor-in-Chief. The author has plagiarized parts of the following papers:  Husain Faiz Karimi,Arini,Siti Ummi Masruroh,Fitri Mintarsi, The Influence of Iteration Calculation Manipulation On Social Network Analysis Toward Twitter's Users Against Hoax In Indonesia With Single Cluster Multi-Node Method Using Apache Hadoop Hortonworkstm Distribution. 2018 6th International Conference on Cyber and IT Service Management (CITSM), PP 1-6.  DOI :10.1109/CITSM.2018.8674374 One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.